A prognostic score to identify low-risk outpatients with acute deep vein thrombosis in the lower limbs - Trujillo-Santos, Javier; Lozano, Francisco; Lorente, Manuel Alejandro; Adarraga, Dolores; Hirmerova, Jana; Del Toro, Jorge; Mazzolai, Lucia; Barillari, Giovanni; Barrón, Manuel; Monreal, Manuel (The American journal of medicine, 2015)
BACKGROUND: No prior studies have identified which patients with deep vein thrombosis in the lower limbs are at a low risk for adverse events within the first week of therapy. METHODS: We used data from the Registro Informatizado de la Enfermedad TromboEmbólica (RIETE) to identify patients at low risk for the composite outcome of pulmonary embolism, major bleeding, or death within the first week. We built a prognostic score and compared it with the decision to treat patients at home. RESULTS: As of December 2013, 15,280 outpatients with deep vein thrombosis had been enrolled. Overall, 5164 patients (34%) were treated at home. Of these, 12 (0.23%) had pulmonary embolism, 8 (0.15%) bled, and 4 (0.08%) died. On multivariable analysis, chronic heart failure, recent immobility, recent bleeding, cancer, renal insufficiency, and abnormal platelet count independently predicted the risk for the composite outcome. Among 11,430 patients (75%) considered to be at low risk, 15 (0.13%) suffered pulmonary embolism, 22 (0.19%) bled, and 8 (0.07%) died. The C-statistic was 0.61 (95% confidence interval [CI], 0.57-0.65) for the decision to treat patients at home and 0.76 (95% CI, 0.72-0.79) for the score (P = .003). Net reclassification improvement was 41% (P < .001). Integrated discrimination improvement was 0.034 for the score and 0.015 for the clinical decision (P < .001). CONCLUSIONS: Using 6 easily available variables, we identified outpatients with deep vein thrombosis at low risk for adverse events within the first week. These data may help to safely treat more patients at home. This score, however, should be validated.
Keywords: Outpatients; hodnocení rizik; Male; Risk Assessment; antikoagulancia; ambulantní péče; prognóza; Ambulatory Care; Adult; dolní končetina; Aged; dospělí; mužské pohlaví; senioři; Venous Thrombosis; Lower Extremity; senioři nad 80 let; lidé; žilní trombóza; ženské pohlaví; Anticoagulants; Humans; pacienti ambulantní; Aged, 80 and over; Prognosis; Female; lidé středního věku; Middle Aged